2020
DOI: 10.3390/molecules25030620
|View full text |Cite
|
Sign up to set email alerts
|

Discovering the Major Antitussive, Expectorant, and Anti-Inflammatory Bioactive Constituents in Tussilago farfara L. Based on the Spectrum–Effect Relationship Combined with Chemometrics

Abstract: Farfarae Flos (FF) is the dried flower bud of Tussilago farfara L, which has antitussive, expectorant, and anti-inflammatory effects. However, little research on the main active composition of FF has been reported. The purpose of this study is to find the main active compounds responsible for the three pharmacological effects (i.e., antitussive, expectorant, and anti-inflammatory effects) of Farfarae Flos, based on the spectrum–effect relationship combined with chemometrics. First, this study uses the UPLC-QDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 22 publications
(23 reference statements)
0
17
0
Order By: Relevance
“…Hierarchical clustering analysis (HCA) is a multivariate analysis method that classifies specimens according to their closeness in nature 4,21 . The analysis maximises the similarity between the comparable data elements and the differences between different data elements 22 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hierarchical clustering analysis (HCA) is a multivariate analysis method that classifies specimens according to their closeness in nature 4,21 . The analysis maximises the similarity between the comparable data elements and the differences between different data elements 22 .…”
Section: Methodsmentioning
confidence: 99%
“…Traditional Chinese medicine (TCM), as a complementary therapy, has survival and quality of life benefits for cancer patients, and has attracted great research interest 2,3 . The detection of one or several index components has been used as the main method in the quality of TCM 4 . However, the multiple chemical components and targets of TCM pose a challenge in establishing quality control methods especially in targeting ingredients associated with clinical efficacy 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…Besides, alkaloids, flavonoids, terpenes and saponins are considered to exert antitussive effects ( Han et al., 2016 ). A series of studies have found that the monomeric components with antitussive bioactivity may be 4,5-O-dicaffeoylquinic acid, caffeic acid, chlorogenic acid, 3,5-O-dicaffeoylquinic acid, 3,4-O-dicaffeoylquinic acid, rutin, kampferol analogues, 2,2-dimethyl-6-acetylchromanone, tussilagone, Bauer-7-ene-3β,16α-diol, β-sitosterol, and sitosterone ( Li et al., 2012 ; Wu et al., 2016 ; Li et al., 2018a ; Yang et al., 2020 ). The antitussive effect of Farfarae Flos has been reported in an animal cough model induced by ammonia.…”
Section: Coughmentioning
confidence: 99%
“…Some mathematical statistical methods have been applied to find the corresponding active components in the spectrum-effect relationship. For example, Liu et al explored the spectrum-effect relationship between fingerprints and three pharmacological effects through gray correlation analysis and partial least square regression, and found the main active components corresponding to the main pharmacological effects of Farfarae Flos [10] . At present, the application of this method in the quality evaluation of SR is limited.…”
Section: Introductionmentioning
confidence: 99%